Strategi Badan Usaha Milik Desa (Bumdes) Perwitasari Dalam Mengembangkan Desa Minapolitan Tambaksari Kecamatan Rowosari - adminjftr adminjftr; 2Yeni Selfia; Ika Agita Sari (Fakultas Teknik dan Rekayasa, 2022)
Tambaksari minapolitan village is a BUMDes fostered village where most of the people cultivate fish in ponds and process the fish in the pond manually. Therefore, a BUMDes strategy is needed to develop Minapolitan villages so that they are advanced and do not lag behind other villages. Qualitative descriptive research describes the condition of Minapolitan village to get the right strategy with SWOT analysis. The results showed that most of the Tambaksari minapolitan community still use manual methods in the cultivation, processing, and marketing of fishpond products. Processed products are less competitive in the market and manual marketing is not yet marketed online, even though some access roads to Tambaksari Village are damaged, so they are lazy to go through them. Therefore, a strategy is needed, including improving access to the village entrance and the road to the pond and adding a gazebo, a unique spot that attracts tourists. Communities also need to be given information technology training to access information on proper fish farming, healthy and durable fish processing, product packaging, and attractive marketing methods. The public is also facilitated in obtaining halal certificates and P-IRT to ensure quality and assure product quality to consumers.